Unlocking the Future of Talent Acquisition: Integrating AI and Innovative Tools for Enhanced Efficiency - Jovanovic, Tatjana (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
As the recruitment landscape becomes increasingly competitive, organizations must adopt innovative tools to improve efficiency and decision-making. The study focuses on a gradual approach to introducing AI-driven technologies and new tools, with a strong emphasis on progressively building TA capabilities to achieve better results. By detailing the real-world implementation, the case highlights the key steps, challenges, and outcomes of this transition, including how the integration of new technologies enhances the recruitment process. The findings demonstrate that a strategic, phased approach to technology adoption improves not only operational efficiency but also candidate experience and overall organizational performance. This case study offers valuable insights for HR professionals and organizations aiming to modernize their TA functions, optimize resource utilization, and stay competitive in a rapidly evolving market.